The impact of a museum-based hazard education program on students, teachers and parents. (March 2017) - MacDonald, Edith; Johnson, Victoria; Gillies, Maureen; Johnston, David
Abstract: Museum-based disaster education programs have the potential to offer hands-on and interactive activities unavailable in schools. In our study, we provide promising new insight into the effectiveness of increasing knowledge and disaster preparedness behaviours in students, teachers, and parents after attending a museum education program. Students from nine primary schools (n=432) attended a disaster education program at the Museum of New Zealand Te Papa Tongarewa and were assigned to one of four treatments or a control group. Three of the treatments groups received "bridging" objects for household disaster preparedness – a fill-in disaster plan, plastic putty or steel brackets - to take home and implement with their families. Pre and post-program questionnaires were administered to students, teachers, and parents. The study found that the museum education program significantly increased student knowledge of disaster preparedness compared to the control group (F4382 =7.657, p<0.001), and had a positive impact on teacher and parent knowledge and behaviour. The results of this study suggest that providing the students a bridging object and instructions they can use themselves at home, even in a limited manner, may help build children's self-efficacy beliefs and skills for preparedness. Implementing a museum-based earthquake education program for schools may increase school and household discussion about disaster preparedness and instigate actions towards preparedness that will ultimately protect lives and property.